Developing multilingual education policies theory, research, practice - Tannenbaum, Michal; Shohamy, Elana Goldberg (Abingdon, Oxon Routledge, Taylor & Francis Group, 2023)
"Multilingual policies are increasingly important and required in educational settings worldwide, yet there lacks a solid experimental body of theory, research and practice, providing guidance for the development of policies. The Israeli context presented in this book serves as a case study or a model that could be used by bodies or entities seeking to devise a multilingual policy. Divided into three parts, the authors begin by addressing the general notion of a multilingual education policy with specific reference to the Israeli context. The book then focuses on specific challenges confronting the new policy that have been explored in empirical studies and concludes with a proposed framework for a new multilingual education policy related to the core theoretical topics and empirical findings discussed in the previous chapters. This framework includes principles and strategies for implementing the process described in the book in other contexts, ensuring wide applicability and relevance. Developing Multilingual Education Policies: Theory, Research, Practice is an essential read for all involved in language policy and planning within Applied linguistics and education"--
Language policy, multilingualism, and education. A new approach to language education policy -- Languages and policy in Israel: history and the present -- Advocating for a new multilingual education policy in Israel -- From policy challenges to research: major issues. Stakeholders' attitudes and perceptions regarding multilingual education policies -- Testing and assessment of minority students: language and content -- Incorporating L1 in the context of teaching English as an additional language -- Connecting Jewish and Arab students via Shared Education -- The role of heritage languages in multilingual education policies -- The linguistic landscape as multilingual awareness -- Conclusions, implementations, and challenges. Principles of the new multilingual education policy -- Conclusions, challenges, and future directions.
Includes bibliographical references and index.
Keywords: Education and state -- Israel; Language policy -- Israel; Multilingual education -- Israel